Analysis of Internal Factors, Performance, Satisfaction, and Loyalty of Farmers Group Members in Seluma District - Zunawarnis Kalbi; Satria Putra Utama; Ketut Sukiyono (UNIVED Press, Dehasen University Bengkulu, 2023)
Eight farmer groups in Rimbo Kedui Village, Seluma Regency, have 220 members. This research aims to: determine the performance of farmer groups; the level of member satisfaction with the performance of the farmer group; analyze factors that influence the level of member satisfaction with performance; analyze the factors that influence the level of loyalty of members towards farmer groups. The research was conducted in September 2019. Data was collected through simple random sampling of 100 members of farmer groups. Data were analyzed using the Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI), and Structural Equation Modeling (SEM)-PLS methods. The research findings show that the overall performance level of each attribute is lower than the average value of members' interest in farmer groups, which reached 74.20%. The farmer group performance variable has a significant influence on the satisfaction variable. Then, the satisfaction variable also significantly influences the loyalty variable. The level of loyalty of farmer group members in Rimbo Kedui Village is within the loyal criteria.